2011
DOI: 10.1007/s12640-011-9256-9
|View full text |Cite
|
Sign up to set email alerts
|

BACE1 Elevation is Involved in Amyloid Plaque Development in the Triple Transgenic Model of Alzheimer’s Disease: Differential Aβ Antibody Labeling of Early-Onset Axon Terminal Pathology

Abstract: β-amyloid precursor protein (APP) and presenilins mutations cause early-onset familial Alzheimer’s disease (FAD). Some FAD-based mouse models produce amyloid plaques, others don’t. β-Amyloid (Aβ) deposition can manifest as compact and diffuse plaques; it is unclear why the same Aβ molecules aggregate in different patterns. Is there a basic cellular process governing Aβ plaque pathogenesis? We showed in some FAD mouse models that compact plaque formation is associated with a progressive axonal pathology inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 35 publications
5
66
0
Order By: Relevance
“…Moreover, we used an antibody directed against N-terminal Aβ (IBL #18584). Previously, in the hybrid 3xTg strain at ages of 2, 14, and 20 months, a monoclonal antibody directed at amino acids 1–5 of the N-terminal Aβ variant (3D6, Elan, South San Francisco, CA, USA) has been used to visualize Aβ deposits (Cai et al 2012). These authors found that 3D6 labels Aβ deposits across the cortex and pyramidal layer in 2-month-old animals, where it appears as perisomatic puncta or granules.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we used an antibody directed against N-terminal Aβ (IBL #18584). Previously, in the hybrid 3xTg strain at ages of 2, 14, and 20 months, a monoclonal antibody directed at amino acids 1–5 of the N-terminal Aβ variant (3D6, Elan, South San Francisco, CA, USA) has been used to visualize Aβ deposits (Cai et al 2012). These authors found that 3D6 labels Aβ deposits across the cortex and pyramidal layer in 2-month-old animals, where it appears as perisomatic puncta or granules.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in APP levels were observed at any time point in any of the genotypes. bsecretase has been implicated in amyloid production and plaque formation (Cai et al, 2011), and its activity is directly related to Ab load Ho et al, 2005). Several authors have proposed that b-secretase cleavage of APP by BACE1 is inhibited by PrP c , and that the absence of PrP c promotes an increase in Ab production, supporting a relationship between b-secretase and PrP c (Kellett and Hooper, 2009;Parkin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous studies regarding AD, the cause and progression of AD are still not well understood. Synaptic dysfunction and axonal pathology that take place prior to the deposition of amyloid plaques and tau aggregation in transgenic AD animal models [1] and the significant reduction in myelination observed within brain areas affected in AD [2] suggest that axonal dysfunction and degeneration represent important components in AD. The maintenance and function of axons and synapses rely on the AT, which keeps axons and nerve terminals supplied with proteins, lipids, and energy, and clears recycled or misfolded proteins to avoid the formation of toxic aggregates.…”
Section: Introductionmentioning
confidence: 99%